Testicular ischemia associated with IgA vasculitis in a child: a case report and literature review - Zhang, Shuya; Wang, Qingwen; Li, Ziwei; Guo, Qingyin (Frontiers in Pediatrics, 2023)
Testicular necrosis is a rare and severe complication of immunoglobulin A (IgA) vasculitis (IgAV). Herein, We report a case of a 10-year-old boy who was admitted to the hospital due to skin purpura and intermittent abdominal pain for 10 days and bilateral testicular pain for 2 days. Scrotal ultrasonography indicated right testicle ischemia, right epididymo-orchitis, and bilateral hydrocele of the testis. Scrotal surgical exploration revealed significant swelling and darkening of the right testicle. Conservative treatment led to improvement in his condition, and he was discharged. During 3 months of follow-up, there was no recurrence of skin purpura or pain, and the urine tests were normal. Color ultrasound indicated only partial blood flow signal to the right testicle tissue, which was slightly smaller than the left testicle. This case highlights the need for continuous attention from clinicians to the signs and symptoms of the reproductive system during the diagnosis and treatment of IgAV. Continuous monitoring with ultrasound can aid in early detection, diagnosis, and treatment of reproductive system lesions of IgA vasculitis.